High tibial osteotomy in geriatric patients with gonarthrosis - Akar, Bedrettin; Oztürkmen, Yusuf; Balioglu, Mehmet B.; Ugur, Fatih; Sükür, Erhan (Springer Science and Business Media LLC, 2025)
BACKGROUND: To evaluate the efficacy of medial opening wedge high tibial osteotomy (MOWHTO) as a treatment modality in geriatric patients aged over 65 presenting with advanced gonarthrosis and severe clinical and functional knee problems. METHODS: A retrospective review was conducted on the medical records of 134 patients aged 65 and older who underwent MOWHTO at our clinic between 2016 and 2022. All patients’ preoperative knee radiographs were independently evaluated by different orthopedic surgeons to assess the degree of osteoarthritis, and deviations in anatomical and mechanical axis values were measured using ortho-radiograms. In cases where radiological imaging posed difficulties in evaluation, classification was performed using magnetic resonance imaging. The surgeries were conducted at a single center. Sixty-six patients with grade III-IV gonarthrosis constituted Group I, while 57 patients with grade I-II gonarthrosis formed Group II. The groups were evaluated clinically and functionally using the Lysholm Knee Scoring Scale, Hospital for Special Surgery Knee-Rating Scale (HSS), and Visual Analog Scale (VAS) preoperatively and at the postoperative sixth, 12th, and 18th months to determine the efficacy of MOWHTO. RESULTS: Group I exhibited significantly higher preoperative and postoperative VAS scores compared to Group II (p = 0.0001). Group II had significantly higher preoperative and postoperative Lysholm and HSS scores than Group I (p = 0.0001). In Group I, seven patients underwent total knee arthroplasty (TKA) within the postoperative first year, and 21 patients within the second year. In Group II, no patients required TKA within the first year, and only three patients required revision to TKA within the second year. In Group I, the main reason for conversion to TKA surgery in 28 patients within the first two years following MOWHTO was the presence of grade IV osteoarthritis according to the Kellgren and Lawrence classification and the age range of 70–75 years. CONCLUSION: MOWHTO is a highly effective procedure for mitigating pain and functional limitations associated with osteoarthritis in geriatric patients with grade I-II gonarthrosis. The efficacy of MOWHTO in patients with grade III-IV osteoarthritis is significantly lower than that in grades I-II, and the treatment method should be selected with caution.
Keywords: Research